A new model and alternative solutions for the description of double layered flexible elements wrapped around a cylinder. (June 2022) - Schumann, P.; Zöllner, R.; Schmidt, T.
Abstract: High-strength fiber ropes have a number of advantages over steel ropes, therefore they currently enjoy great research interest in conjunction with rope winches. However, what is lacking in the art are suitable drives, since concepts for steel ropes cannot be easily transferred to high-strength fiber ropes. A promising innovative principle is the belt wrap capstan, although adequate and validated models for predicting optimal rope force with the lowest possible belt force are still missing. This paper aspires to contribute towards closing this gap by presenting a validated model of a double layered belt wrap capstan First, a general law of friction is considered. Then, special focus is given to power law friction. This law of friction implies the zero force phenomenon which is also discussed. Highlights: A belt wrap capstan for high-strength fiber ropes was developed and patented. Paper presents a model for double layered belt wrap capstan (theory and validation). On theoretical side, general law of friction is discussed; focus on power law. Characteristic phenomenon referring to forces for certain limit cases described. Method to find approximate analytical solutions for ordinary differential equations.